Knowledge integration and innovation critical challenges facing international technology-based firms - Berggren, Christian, 1950- (Oxford : Oxford University Press, 2011)
Innovation processes have increasingly become interdisciplinary collaborative, inter-organizational, and international. Based on empirical studies, this book examines how this integration of knowledge has become essential to firms in enabling innovation particularly crucial in technology-based industries.
Title from home page (viewed on Sept. 5, 2011).
Also issued in print format.
Includes bibliographical references and index.
Keywords: Technological innovations; Organizational change; Knowledge management